Pengaruh Persepsi pada Kreativitas Guru dalam Penggunaan Media Belajar dan Iklim Sekolah terhadap Prestasi Belajar Peserta Didik Mata Pelajaran Ekonomi di SMK Swasta Jakarta Selatan - Ani Interdiana Candra Sari; Fadli Rasam; Elin Karlina (Universitas Indraprasta PGRI Jakarta, 2022)
The purpose of this study is to obtain answers empirically the effect of (1) teacher creativity in the use of learning media and school climate on student learning achievement simultaneously, (2) teacher creativity in using learning media on student learning achievement partially, (3) school climate on student learning achievement partially. This research was conducted at South Jakarta Private Vocational High School with 100 students as respondents. The method used is a survey with multiple linear regression analysis approach. Based on the research and calculation of SPSS, the following research results were obtained: (1) there was an influence of teacher creativity in the use of learning media and school climate on student learning achievement simultaneously. (2) There was a partial effect of teacher creativity in the use of learning media on student learning achievement (this indicates that the more creative and varied the media used by teachers in learning was proven to increase students' enthusiasm and learning achievement). (3) There was a partial influence of school climate on learning achievement (this indicates that the more comfortable and conducive the classroom atmosphere is proven to increase the learning achievement of students). Teachers' expertise in managing learning media will make students enthusiastic and interest in them to be active in the learning process so that it will affect student learning achievements.